Spatial and temporal distribution of oak wilt in golden‐cheeked warbler habitat - Laura R. Stewart; Michael L. Morrison; David N. Appel; R. Neal Wilkins (Wildlife Society Bulletin)
ABSTRACT Research suggests the presence of oak wilt in Ashe juniper–oak (Juniperus ashei–Quercus spp.) woodland has a negative effect on habitat selection and quality for the federally endangered golden‐cheeked warbler (Setophaga chrysoparia). We used aerial imagery and an occupancy model to estimate the amount of golden‐cheeked warbler habitat within our study region in Texas, USA, that was affected by oak wilt over a 10‐year timeframe, 2008–2018, and to assess the current probability of warbler occupancy in areas affected by oak wilt prior to 1983. We also quantified vegetation characteristics to assess regeneration in areas affected by the disease. Our results indicate that oak wilt frequently occurs in golden‐cheeked warbler habitat and will continue to spread into warbler habitat in the coming years. We estimated that 6.9% of golden‐cheeked warbler habitat within our study region in the southwestern portion of the warbler's range was affected by oak wilt in 2008. By 2018, we predict that 13.3% of golden‐cheeked warbler habitat will be affected by the disease. Areas affected by oak wilt prior to 1983 were less likely to be classified as current potential warbler habitat than were unaffected areas. We found no differences between the understory vegetation of affected and unaffected areas but, in general, oaks were more common in the overstory than in the understory, suggesting that species composition in affected areas may shift following an outbreak of oak wilt. Future management efforts should address the threat oak wilt poses to golden‐cheeked warblers by incorporating applicable preventative measures. © 2014 The Wildlife Society.